2016
DOI: 10.1111/ejn.13289
|View full text |Cite
|
Sign up to set email alerts
|

Individual neurons in the caudal fastigial oculomotor region convey information on both macro‐ and microsaccades

Abstract: Recent studies have suggested that microsaccades, the small amplitude saccades made during fixation, are precisely controlled. Two lines of evidence suggest that the cerebellum plays a key role not only in improving the accuracy of macrosaccades but also of microsaccades. First, lesions of the fastigial oculomotor regions (FOR) cause horizontal dysmetria of both micro-and macrosaccades. Secondly, our previous work on Purkinje cell simple spikes in the oculomotor vermis (OV) has established qualitatively simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Another explanation is physiological and lies upon the fluctuations of the activity of neurons, which, from the foveal ganglion cells to the saccade-related premotor burst neurons, exhibit sustained firing rates whenever gaze is held stable. Among this immense number of neurons, we find not only long-lead burst neurons in the pontine reticular formation, but also neurons in the caudal fastigial nucleus (Kleine et al 2003;Sun et al 2016). After unilateral inactivation of this nucleus, fixational saccades are not only dysmetric (Guerrasio et al 2010), but the direction of gaze during fixation and pursuit is also always deviated towards the lesioned side (Bourrelly et al 2018;Goffart et al 2004;Guerrasio et al 2010).…”
Section: Discussionmentioning
confidence: 85%
“…Another explanation is physiological and lies upon the fluctuations of the activity of neurons, which, from the foveal ganglion cells to the saccade-related premotor burst neurons, exhibit sustained firing rates whenever gaze is held stable. Among this immense number of neurons, we find not only long-lead burst neurons in the pontine reticular formation, but also neurons in the caudal fastigial nucleus (Kleine et al 2003;Sun et al 2016). After unilateral inactivation of this nucleus, fixational saccades are not only dysmetric (Guerrasio et al 2010), but the direction of gaze during fixation and pursuit is also always deviated towards the lesioned side (Bourrelly et al 2018;Goffart et al 2004;Guerrasio et al 2010).…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, neurons in the posterior vermis, caudal fastigial nucleus, and interpositus nucleus of the cerebellum are related to the precise and adaptive control of saccades (Robinson and Fuchs, 2001; Dash and Thier, 2014). Recent studies reported that single neurons in the oculomotor vermis and caudal fastigial nucleus discharged both for macro- and micro-saccades (Arnstein et al, 2015; Sun et al, 2016). We previously reported that neurons in the monkey PPTg showed saccade-related activity modulation, some modulations were only associated with reward-related saccades consistent with neurons reported in the basal ganglia (Kobayashi et al, 2002; Okada and Kobayashi, 2009), while others exhibited this modulation with every saccade, including small fixational saccades, consistent with neurons in the cerebellum (Okada and Kobayashi, 2014).…”
Section: Therapeutic Effect Of Pptg Stimulation In Parkinson’s Diseasementioning
confidence: 99%
“…Under this hypothesis, neurons should fire early for contraversive saccades, helping to accelerate the eye, whereas the delayed firing of ipsiversive neurons serves to decelerate and stop the eye at saccade termination. However, new data reported by Sun et al (2016) call this view into question.Sun and colleagues recorded single-unit cFN neuron activity while primates made saccades of various magnitudes. These saccades included very small saccades, made during periods of fixation (microsaccades), as well as larger magnitude goal-directed saccades to peripheral targets.…”
mentioning
confidence: 99%
“…Under this hypothesis, neurons should fire early for contraversive saccades, helping to accelerate the eye, whereas the delayed firing of ipsiversive neurons serves to decelerate and stop the eye at saccade termination. However, new data reported by Sun et al (2016) call this view into question.…”
mentioning
confidence: 99%
See 1 more Smart Citation